Structural Design Optimization and Prestress Simulation of the Laminate-Containment Launcher - Wang, Jun; Li, Baoming (IEEE transactions on plasma science, 2021)
The laminate-containment launcher is a high-efficiency electromagnetic railgun launcher (EMRL), which uses a laminate structure to reduce eddy current loss. However, the research on the design optimization of the laminate-containment launcher with prestress and mass as the goal is rarely mentioned. In this article, some key parameters of the laminate-containment launcher-the magnitude of interference s , the axial thickness of the steel laminate t_{s} and insulation laminate t_{i} , the thickness of inner glass fiber r_{g} , and the radial thickness of the laminate r_{l} -are studied. On this basis, the influence of the five parameters on the hoop stress of the rail is fitted as a function by using the multiple nonlinear regression method. Then, the maximum hoop stress f_{1max} and the maximum hoop stress difference f_{2max} of the rail are calculated by using a nonlinear programming algorithm. Finally, the maximum hoop stress f_{1max} , the maximum hoop stress difference f_{2max} , and the maximum mass f_{3max} are taken as the reference values, and the optimal solution of the multiobjective function is obtained by using the weighted nonlinear programming algorithm. The results can be described as follows: the hoop stress of the rail changes linearly with the increase of the magnitude of interference, while the hoop stress changes approximately quadratic with the change of other parameters. Through the optimization of nonlinear programming algorithm with weighted form, the optimal design under different weighted values is obtained, which has a small error compared with the calculation results of ANSYS. The important characteristic that the hoop stress of the laminate-containment launcher presents wavy variation along the axial direction is obtained by numerical simulation. These results can provide theoretical guidance for the structural design of the laminate-containment launcher.